2020
DOI: 10.5812/zjrms.89021
|View full text |Cite
|
Sign up to set email alerts
|

Useful Effects of Curcumin Supplementation on Gastric Superoxide Dismutase Activity and Serum Malondialdehyde Level During Endurance Training in Male Wistar Rats

Abstract: Background: Strenuous endurance training triggers the antioxidant defenses of the body and attempts to find supplements to heal gastric ulcers induced by strenuous endurance training and increased body oxidant status. Objectives: Therefore, the current study aimed at investigating the effects of curcumin supplementation during nine weeks of endurance training on gastric antioxidant capacity (superoxide dismutase; SOD) and serum lipid peroxidation (malondialdehyde; MDA) in male Wistar rats. Methods: The current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…The attenuating effect of turmeric rhizome powder was more than that of omeprazole here. This is in line with previous studies which presented that curcumin supplementation increased gastric SOD enzyme activity and thereby restores the antioxidant defense of tissues and body (Gorzi & Asadi, 2020).…”
Section: Resultssupporting
confidence: 93%
“…The attenuating effect of turmeric rhizome powder was more than that of omeprazole here. This is in line with previous studies which presented that curcumin supplementation increased gastric SOD enzyme activity and thereby restores the antioxidant defense of tissues and body (Gorzi & Asadi, 2020).…”
Section: Resultssupporting
confidence: 93%
“…Our data demonstrated significant increases in AChE activity in the SOL muscle in accordance with the results of the Gorzi et al (2013), which have evaluated A12 isoform of AChE after endurance training with running. In that study, the authors suggested that the increased AChE activity related to augment resistance to fatigue was due to the higher storage capacity and consequently greater release of acetylcholine in the neuromuscular junction by motoneurons (Gorzi et al, 2013). According to Navarrete & Vrbova (1983), large magnitude adaptations to the exercise are expected as the isometric contraction of the slow contraction muscles are tonically activated.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, denervation induces the AChE activity and expression and elicits the loss of muscle mass (Decker & Berman, 1990). In contrast, rats submitted to running can show increased AChE activity (Gorzi et al, 2013). Again, this enzymatic alteration seems to occur in parallel to zoometric changes induced by exercise as this exercise protocol can induce muscle mass gain in rats (Bonnet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione peroxidase level was measured by the method as reported by Abarikwu et al [28]. Superoxide dismutase level was measured by the method as reported by Gorzi and Asadi [29]. Catalase level was measured by the method as reported by Safaeian et al [30].…”
Section: Measurement Of Mda Gpx Sod and Catalasementioning
confidence: 99%